The Impact of Climate Change on Work Lessons for Developing Countries - Moustafa Feriga; Nancy Lozano Gracia; Pieter Serneels (Institute of Labor Economics (IZA), 2024)
This paper identifies five areas where climate change may impact work and draws lessons for developing countries by reviewing the evidence. Firstly, demand for labor is unevenly affected, with agriculture, heat-exposed manufacturing, and the brown energy sector experiencing downturns, while other sectors may see a rise, resulting in an uncertain overall impact. Secondly, climate change impacts labor supply through absenteeism, shirking, and altering work-time patterns, depending on the activity and sector. Thirdly, productivity may decline, especially in heat-exposed industries, primarily due to health reasons. Fourthly, heightened earnings variability likely increases vulnerability among the self-employed. Fifthly, climate change can influence labor allocation and catalyze sectoral reallocation. Higher temperatures are also linked to increased migration. But caution is needed in interpreting these findings, as studies across these topics predominantly use fixed effect estimation and concentrate on short-term impacts, neglecting adaptation. Emerging research on adaptation indicates that workplace cooling is unappealing for firms with narrow profit margins, while coping strategies of farms and households have unclear optimality due to adoption barriers. Government responses remain understudied, with six potential areas identified: green jobs, green skills, labor-oriented adaptation, flexible work regulation, labor market integration, and social protection. The paper concludes by outlining future research directions.
Keywords: Q54; J01; O1; 330; development; labor; climate change